TI_GERICHTE 52.2018.299 vom 17. Mai 2018 , Proposta da parte del Municipio di acquisto di uno scorporo di un terreno - TI Tribunale d'appello (2018)
Proposta da parte del Municipio di acquisto di uno scorporo di un terreno